Transition to competent oral feeding in preterm infants: Analyzing timing and determinants - Gabriela Bolea Muguruza; Cristina de Frutos Martínez; M. Teresa Tamayo Martínez; Judith Martín Corral (Anales de Pediatría (English Edition))
Introduction: The achievement of oral feeding competence (OFC) is a challenge in preterm infants and can be affected by several factors. Objective: The aim of our study was to determine the time elapsed to development of OFC in very low birth weight (VLBW, weight < 1500 g) preterm infants and to identify factors associated with greater difficulty in achieving this skill. Population and methods: Observational, longitudinal and prospective study in VLBW infants over a period of 7 years (2016–2022). We collected data on perinatal variables, feeding practices and complications associated with prematurity. We analyzed the number of days needed to achieve OFC and which variables predicted greater delay in achieving OFC. Results: We included 145 VLBW infants with a median gestational age (GA) of 29 weeks with a weight of 1247 g. Oral feeding was initiated at 33.6 weeks (SD, 1.2) and full oral feeding was achieved at 35.9 weeks (SD, 1.9). The median time to achievement of OFC was 15 days (8–22.5). The variables associated with longer delay of OFC were severe combined morbidity (24 vs 14 days; P < .001) and moderate/severe bronchopulmonary dysplasia (23 vs 14 days; P < .001). In infants without severe combined morbidity, we found no differences in the days elapsed to achievement of OFC between those born before or after 28 weeks of GA (P = .131). Conclusions: Our findings highlight the importance of structuring the transition to oral feeding and identifying the most at-risk group, which in our study were infants with severe morbidity associated with prematurity, for the purpose of targeting potential interventions. Resumen: Introducción: La adquisición de la competencia para la alimentación oral (CAO) representa un desafío en RN prematuros y puede verse afectada por diversos factores. Objetivo: Es conocer el tiempo necesario para adquirir la CAO en RN <1500 g (RNMBP) e identificar factores asociados a mayor dificultad para alcanzar dicha habilidad. Población y métodos: Estudio observacional, longitudinal y prospectivo durante 7 años (2016-2022) en RNMBP. Se registran variables perinatales, prácticas de alimentación y complicaciones asociadas a la prematuridad. Se analiza número de días necesarios para alcanzar la CAO y qué variables permiten predecir la necesidad de más tiempo para conseguir dicha competencia. Resultados: Se incluyen 145 RNMBP con una mediana de edad gestacional (EG) 29 s y peso 1247 g. La alimentación oral se inicia a las 33.6 ± 1.2 s y se completan todas las tomas por boca a las 35.9 ± 1.9 s La CAO se consigue en una mediana de 15 días (8-22.5). Las variables asociadas a un tiempo más prolongado para alcanzar la CAO fueron: morbilidad combinada grave (MCG) (24 vs. 14 días; p < 0.001) y DBP moderada-grave (23 vs.14 días; p < 0.001). En la población sin MCG, no se encontraron diferencias en número de días para la CAO en función de EG menor o mayor de 28 s (p = 0.131). Conclusiones: Resaltamos la importancia de estructurar el proceso de transición a la alimentación oral e identificar a la población de más riesgo, que en nuestro estudio fueron los niños con morbilidad grave independientemente de la edad gestacional, para dirigir a ellos las posibles intervenciones.